Current Slip and Strain Rate Distribution Along the Ganzi-Yushu-Xianshuihe Fault System Based on InSAR and GPS Observations - Zhang, Wenting; Ji, Lingyun; Zhu, Liangyu; Liu, Chuanjin; Jiang, Fengyun; Xu, Xiaoxue (Frontiers in Earth Science, 2022)
The Ganzi-Yushu-Xianshuihe fault (GYXSF), a large strike-slip fault located on the east side of the Tibetan Plateau, has seen high seismic activity in recent years. However, despite the earthquake risk posed by this fault, there is a lack of high-resolution geodetic survey results regarding the current slip rate. We have used 4-track ascending and 5-track descending Sentinel-A/B SAR Interferometric Synthetic Aperture Radar (InSAR) data from 2014 to 2020, to obtain the current slip rate of the entire GYXSF within the radar’s line of sight (LOS), with high resolution. Both InSAR and published Global Positioning System (GPS) data were integrated to calculate a high-resolution 3-dimensional deformation field and strain rate field of the GYXSF. We have also used the screw dislocation model to calculate current slip rates in the fault-parallel direction at 20 km intervals. The key findings of our study are as follows. (1) The current slip rate of the GYXSF is segmental; the slip rate of the Ganzi-Yushu fault (GYF) gradually increases from ~1 to ~ 6 mm/yr from the north-west to the southeast, while the slip rate of the Xianshuihe fault (XSF) increases from ~8.5 to ~ 12 mm/yr from the north-west to the southeast. (2) There are non-negligible post-earthquake deformations along the GYXSF, and our best fitting results show that an approximately 100 km long section of the GYF has undergone post-seismic after-slip in the 4–10 years since the 2010 Yushu M 6.9 earthquake, with a maximum creep of ~2.2 mm/yr. (3) The strain rate is dispersed in the GYF region but concentrated on the fault in the XSF region. There is also a measurable strain rate on secondary faults north of the GYXSF; the seismic hazard of these secondary faults cannot be ignored. (4) The continuous deformation and blocky-like models are the best models to explain the observations and deformation characteristics of the GYF and XSF, respectively.